Sensorless and independent speed control of dual-PMSM drives using five-leg inverter (FLI) - Jurifa, Mat Lazi (2016)
This research aims to develop and implement a combined sensorless and independent speed control for dual-PMSM (Permanent Magnet Synchronous Motor) drives fed by a single Five-Leg Inverter (FLI). Dual-motor drives are widely used in high traction power industry such as propulsion system, aircraft, locomotive, Hybrid Electric Vehicle (HEV) and others. In general, dual-motor drives are designed to reduce size and cost with respect to single motor drives. However, dual-motor drives using a single three-leg inverter has its limitation in the case of operation at different operating conditions and independent speed control requirement. Recent research has shown that, dual motor drives can be independently controlled by using Five-Leg inverter (FLI). By employing this FLI topology, the dual-motor drives can be used for four-quadrant control, variable speed operation and load disturbance rejection. In other words, it can be operated for different applications. In the case of conventional dual-PMSM drives, the drives system still requires current sensors and voltage transducers for speed and rotor position estimation. In PMSM drives, the information of the feedback speed and rotor angular position is compulsory. Therefore, this research is trying to implement a combined sensorless and independent speed control for dual PMSM drives system and at the same time eliminating the usage of voltage transducers. This thesis investigates the behavior of sensorless and independent speed control for Dual-Permanent Magnet Synchronous Motor (PMSM) drives. Initially, a single PMSM drives is designed and simulated, followed by the development of Dual-PMSM drives model. The speed and current controllers are implemented in d-q rotor reference frame using Simulink/MATLAB and the switching signals are generated by the built-in function and dSPACE. Then, the sensorless drive system is developed based on adaptive speed and position estimator. The overall performance of the drives is investigated and evaluated in terms of speed responses overshoot under variation of speed reference and speed drop under load torque disturbances. The simulation results have proved that the performance characteristics of sensorless dual-PMSM are almost similar with system using sensor except during the start-up condition. The motor performance is degraded in terms of speed overshoot for small and medium speed reference or when the motor operates far from the designed operating condition (rated value). The proposed independent dual-PMSM drives fed by FLI have better load rejection capability compared with conventional dual-PMSM drives fed by single three-phase inverter. The experimental results of the drives under investigation have shown acceptable correlation between the theoretical and simulation.